DOI: 10.17077/etd.1msv1jd9
|View full text |Cite
|
Sign up to set email alerts
|

On-line supervision of school counselors

Abstract: This study examined the supervision effectiveness of three online peer supervision models as measured by the two outcome variables of case conceptualization skills and self-efficacy. Also, it explored the impact of developmental levels of school counselors on the outcomes of supervision. Practicing school counselors from a national sample were randomly assigned to three groups: the Online Structured Peer Supervision Group (S group), the Online Peer Discussion Group (D group), and the Control Group (C group). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…With regard to the school context, Bodenhorn, Wolfe, and Airen (2010) reported that school counsellor self-efficacy is an important factor for students, as a school counsellor with high selfefficacy is likely to have a better effect on students. In the United States, school counsellor selfefficacy has been studied as a subtopic with regard to different circumstances, such as supervision (Cinotti, 2013;Lin, 2012), burnout (Gunduz, 2012), ethical knowledge (Mullen, Lambie, Griffith, & Sherrell, 2016), and school climate (Sutton & Fall, 1995). Numerous studies have also revealed the significant preventive role of counsellors in school settings, such as a detrimental school climate (e.g., Hernández & Seem, 2004), as well as traditional bullying (e.g., Bauman, 2008;Jacobsen & Bauman, 2007) and cyberbullying (e.g., Bhat, 2008).…”
Section: Counselling Self-efficacymentioning
confidence: 99%
“…With regard to the school context, Bodenhorn, Wolfe, and Airen (2010) reported that school counsellor self-efficacy is an important factor for students, as a school counsellor with high selfefficacy is likely to have a better effect on students. In the United States, school counsellor selfefficacy has been studied as a subtopic with regard to different circumstances, such as supervision (Cinotti, 2013;Lin, 2012), burnout (Gunduz, 2012), ethical knowledge (Mullen, Lambie, Griffith, & Sherrell, 2016), and school climate (Sutton & Fall, 1995). Numerous studies have also revealed the significant preventive role of counsellors in school settings, such as a detrimental school climate (e.g., Hernández & Seem, 2004), as well as traditional bullying (e.g., Bauman, 2008;Jacobsen & Bauman, 2007) and cyberbullying (e.g., Bhat, 2008).…”
Section: Counselling Self-efficacymentioning
confidence: 99%
“…Despite the steady increase in technology, only limited research specifically examined synchronous (concurrent interfacing) online supervision, and, in particular, such supervision of school counseling (Bender & Dykeman, 2016). Most existing research focused on counselor education skill delivery (Conn et al, 2009; Trepal et al, 2011) and peer consultation (Lin, 2012; Paulson et al, 2015). In the literature that is available for both asynchronous (nonconcurrent interaction, such as email or chat) and synchronous supervision, an overarching theme is that providing online supervision is a way of creating access to professional development for those who otherwise would not be able to participate (Perera-Diltz & Mason, 2012).…”
Section: School-counseling-specific Supervisionmentioning
confidence: 99%